EFFECTIVE ASPECTS OF APPLYING METACOGNITIVE METHODS TO UNIVERSITY STUDENTS - Khushnazarova, M.N.; Rasulov, E.M. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
The article presents a look at the reforms that are being carried out to further improve and develop the higher education system in our country, and the effective aspects of using metacognitive methods in higher education institutions.
Keywords: higher education system; metacognitive; skill; method; reflection